Upaya Peningkatan Kualitas Pelayanan dalam Meningkatkan Minat Jamaah Umrah Sultan Trip Holidays - Muhammad Rafiq; Asyari Asyari (Business and Economic Publication, 2026)
The increasing competition in the Umrah travel industry requires service providers to continuously improve service quality in order to maintain pilgrims' interest. Previous studies generally discuss service quality in a broad context, while limited research specifically examines personalized service strategies and technology-based services in local Umrah travel agencies. This study aims to analyze efforts to improve service quality in increasing the interest of Umrah pilgrims at Sultan Trip Holidays Bukittinggi. This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that pilgrims' interest is influenced by several main strategies, including the recruitment of professional and responsive human resources, continuous staff training, empathy-based services, accessible digital information services, and the provision of comfortable travel facilities. The study highlights that the combination of personalized services and the utilization of technology serves as a distinguishing factor that strengthens pilgrims' trust and interest in Sultan Trip Holidays.